1999
DOI: 10.1111/j.1540-8167.1999.tb00638.x
|View full text |Cite
|
Sign up to set email alerts
|

Bezold‐Jarisch‐Like Reflex During Radiofrequency Ablation of the Pulmonary Vein Tissues in Patients with Paroxysmal Focal Atrial Fibrillation

Abstract: RF catheter ablation of the pulmonary vein tissues could evoke a variety of profound bradycardia-hypotension responses. The Bezold-Jarisch-like reflex might be the underlying mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 18 publications
0
36
1
Order By: Relevance
“…17 In another study, 10 transient autonomic dysfunction was observed after focal PV ablation in 37 patients, and in 6 of them, vagal reflexes were elicited but not deliberately ablated; however, there were no differences in HRV or recurrences between those with and without reflexes. This may represent methodological differences in the ablation procedure or the smaller scale of these studies.…”
Section: Parasympathetic Modification and Recurrence Of Af After Cpvamentioning
confidence: 99%
See 1 more Smart Citation
“…17 In another study, 10 transient autonomic dysfunction was observed after focal PV ablation in 37 patients, and in 6 of them, vagal reflexes were elicited but not deliberately ablated; however, there were no differences in HRV or recurrences between those with and without reflexes. This may represent methodological differences in the ablation procedure or the smaller scale of these studies.…”
Section: Parasympathetic Modification and Recurrence Of Af After Cpvamentioning
confidence: 99%
“…Previous studies have demonstrated parasympathetic nerve terminals in the PV area, and the incidence of ablationinduced bradycardia-hypotension response was higher in PV areas than with ablation of other atrial tissues. [17][18][19][20] Hsieh et al 10 reported severe bradycardia and hypotension in 6 of 37 patients undergoing focal PV ablation. In their study, the ablation site was inside the left superior PV (4 patients) or inside the right superior PV (2 patients).…”
Section: Location and Abolition Of Vagal Reflexesmentioning
confidence: 99%
“…10 Thereafter, we also decreased the maximal temperature to 50°C to 55°C during the following energy applications. The ablation end point was total elimination or marked reduction (Ͻ50% of the initial amplitude) of ectopic focus amplitude.…”
Section: Radiofrequency Catheter Ablationmentioning
confidence: 99%
“…Recently, RF catheter ablation of pulmonary veins (PVs) has been demonstrated to cure focal atrial fibrillation (AF). [7][8][9][10] However, transient sinus bradycardia, sinus arrest, and hypotension have been reported as complications during focal ablation of PVs, and thermal stimulation of vagus nerve fibers might play an important role in these complications. 9 Therefore, the purpose of the present study was to evaluate the effects of focal PVs ablation on autonomic function by using HRV.…”
mentioning
confidence: 99%